Analysis of the powers of the prosecutor in article 291 of the CCP - Торбас Олександр Олександрович; Торбас Александр Александрович; Torbas Oleksandr O. (My University, 2013)
This article analyzes the powers of the prosecutor in the criminal production verification and confirmation of the indictment on the pre-trial investigation. Assessment about the importance of changing the name of the indictment was made. Comparison of similar articles of the CCP in 1960 and 2012 was conducted. Necessity of the extensive interpretation of the Article 291 of the CCP was established. Conclusion about key role of the prosecutor was made.

У статті аналізуються повноваження прокурора в кримінальному перевірки виробництва і затвердження обвинувального висновку на досудового слідства. Була зроблена оцінка важливості зміни назви обвинувального висновку. Було проведено порівняння аналогічних статей КПК в 1960 і 2012 роках. Встановлена необхідність широкого тлумачення статті 291 КПК. Був зроблений висновок про ключову роль прокурора.

В данной статье анализируются полномочия прокурора по уголовному производству и подтверждение обвинительного заключения о досудебном расследовании. Была сделана оценка важности изменения названия обвинительного заключения. Сопоставлены аналогичные статьи КПК в 1960 и 2012 гг. Была установлена необходимость широкого толкования статьи 291 УПК. Был сделан вывод о ключевой роли прокурора.
Torbas O.O. Analysis of the powers of the prosecutor in article 291 of the CCP / O.O. Torbas // Науковий журнал «Молодий вчений». – 2015. - №12.1. – С. 147-150.
Keywords: prosecutor; investigator; indictment; materials of criminal proceedings; approval of indictment; closing criminal proceeding; прокурор; слідчий; обвинувальний акт; матеріали кримінальної справи; затвердження обвинувального акту; закриття кримінальної справи; прокурор; следователь; обвинительный акт; материалы уголовного дела; утверждение обвинительного акта; закрытие уголовного дела